GSK-3β phosphorylation and alteration of β-catenin in hepatocellular carcinoma - Ban, Ke Chen; Singh, Harjit; Krishnan, R.; Seow, Heng Fong (Elsevier Ireland, 2003)
The aim of this study is to investigate the potential correlation between the expression of phosphorylated glycogen synthase kinase-3β (phospho-GSK-3β) and β-catenin, and the mutations of β-catenin gene at the consensus GSK-3β phosphorylation site. The reason for this approach is to gain a better understanding of the molecular mechanisms of hepatocarcinogenesis in Malaysia. The expression of phospho-GSK-3β and β-catenin by immunohistochemistry and the mutations of β-catenin were studied in 23 hepatocellular carcinoma (HCC) and surrounding tissues. Overexpression of phospho-GSK-3β and β-catenin was found in 12/23 (52.2%) and 13/23 (56.5%) in HCC tissues, 6/23 (26.1%) and 9/23 (39.1%) in surrounding tissues, respectively. Overexpression of β-catenin in HCC tissues compared to the surrounding liver tissue was found to be higher in HCC tissues (p=0.015). In addition, we found that the expression of phospho-GSK-3β was related with the accumulation of β-catenin in surrounding tissues (p<0.05). The expression of phospho-GSK-3β and its association with the development of HCC is reported for the first time. In addition, this is the first report from Malaysia which shows that there are no mutations at the GSK-3β consensus phosphorylation sites on β-catenin gene in all 23 paired HCC and surrounding tissues. This result differed from HCC in geographical areas with high aflatoxin exposure.